A Broad G Protein-Coupled Receptor Internalization Assay that Combines SNAP-Tag Labeling, Diffusion-Enhanced Resonance Energy Transfer, and a Highly Emissive Terbium Cryptate - Levoye, Angélique; Zwier, Jurriaan M.; Jaracz-Ros, Agnieszka; Klipfel, Laurence; Cottet, Martin; Maurel, Damien; Bdioui, Sara; Balabanian, Karl; Prézeau, Laurent; Trinquet, Eric; Durroux, Thierry; Bachelerie, Françoise (Frontiers in Endocrinology, 2015)
Although G protein-coupled receptor (GPCR) internalization has long been considered as a major aspect of the desensitization process that tunes ligand responsiveness, internalization is also involved in receptor resensitization and signaling, as well as the ligand scavenging function of some atypical receptors. Internalization thus contributes to the diversity of GPCR-dependent signaling, and its dynamics and quantification in living cells has generated considerable interest. We developed a robust and sensitive assay to follow and quantify ligand-induced and constitutive-induced GPCR internalization but also receptor recycling in living cells. This assay is based on diffusion-enhanced resonance energy transfer (DERET) between cell surface GPCRs labeled with a luminescent terbium cryptate donor and a fluorescein acceptor present in the culture medium. GPCR internalization results in a quantifiable reduction of energy transfer. This method yields a high signal-to-noise ratio due to time-resolved measurements. For various GPCRs belonging to different classes, we demonstrated that constitutive and ligand-induced internalization could be monitored as a function of time and ligand concentration, thus allowing accurate quantitative determination of kinetics of receptor internalization but also half-maximal effective or inhibitory concentrations of compounds. In addition to its selectivity and sensitivity, we provided evidence that DERET-based internalization assay is particularly suitable for characterizing biased ligands. Furthermore, the determination of a Z′-factor value of 0.45 indicates the quality and suitability of DERET-based internalization assay for high-throughput screening (HTS) of compounds that may modulate GPCRs internalization.